New record of the pea crab Nepinnotheres villosulus (Guérin-Meneville, 1831) (Brachyura: Pinnotheridae) from clams and cockles of Pakistan (northern Arabian Sea). (14th September 2015) - Jahangir, Shahnaz; Siddiqui, Ghazala; Ayub, Zarrien; Boyko, Christopher B.
Abstract : The pea crab Nepinnotheres villosulus is recorded for the first time from Sonmiani, Pakistan. It was found in six species of clams, Meretrix casta, Marcia recens, Callista umbonella, Gastrana multangula, Protapes cor and Psammotreta angulata and in one species of blood cockle, Anadara antiquate, with the highest prevalence in Meretrix casta . In some clams, both male and female crabs were found inside the host. More than 60% of female crabs were soft-shelled and ovigerous.